Quantitative corpus linguistics with R a practical introduction - Gries, Stefan Thomas, 1970- (Routledge, 2009)
The first textbook of its kind, Quantitative Corpus Linguistics with R demonstrates how to use the open source programming language R for corpus linguistic analyses. Computational and corpus linguists doing corpus work will find that R provides an enormous range of functions that currently require several programs to achieve ? searching and processing corpora, arranging and outputting the results of corpus searches, statistical evaluation, and graphing.